2019
DOI: 10.14423/smj.0000000000000974
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Pediatric Cervical Spine Injuries in Iraq and Afghanistan

Abstract: Cervical spine injuries in pediatric trauma patients are uncommon, and subsequently, proper diagnosis and the efficacy of spinal motion restriction in these patients remain a subject of contention. The aim of this study was to describe the incidence of cervical spine injuries in pediatric patients in Iraq and Afghanistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Pediatric patients with SCI are currently underserved in their access to cervical collars 49 . In a national study of pediatric trauma encounters in the United States, 83% of pediatric patients with cervical spine fractures did not have a prehospital cervical collar placed 49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric patients with SCI are currently underserved in their access to cervical collars 49 . In a national study of pediatric trauma encounters in the United States, 83% of pediatric patients with cervical spine fractures did not have a prehospital cervical collar placed 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Pediatric patients with SCI are currently underserved in their access to cervical collars 49 . In a national study of pediatric trauma encounters in the United States, 83% of pediatric patients with cervical spine fractures did not have a prehospital cervical collar placed 49 . Lack of pediatric‐sized equipment plays a role in the underuse of cervical collars in pediatric patients with potential SCI, 49 necessitating the development of a clinical decision tool to guide cervical collar placement in pediatric patients with SCI or at risk of developing SCI.…”
Section: Resultsmentioning
confidence: 99%
“…There were 48.3% who had ICH that was not specified 44 . Although head injuries are the most common cause of trauma, spinal injuries are rare, with only 1% of pediatric patients being reported with a cervical spine fracture and 20% of those having spinal cord involvement 45 …”
Section: Discussionmentioning
confidence: 99%
“…44 Although head injuries are the most common cause of trauma, spinal injuries are rare, with only 1% of pediatric patients being reported with a cervical spine fracture and 20% of those having spinal cord involvement. 45 One currently controversial in-hospital treatment involves delivering an excess supply of oxygen. Naylor found that hyperoxia occurred in 22% of pediatric casualties, but no mortality difference was noted.…”
Section: Critical Carementioning
confidence: 99%